Impact Of The Ownership Characteristics On Investment Efficiency: Mediating Role Of Frq - Asiya Khattak , Fakhra Aslam , Surayya Jamal , Dania Marium , Majid Mumtaz (Migration Letters, 2024)
The current study aimed to analyze the mediating role of financial reporting quality between the impact of ownership characteristics and investment efficiency in Pakistan while considering non-financial firms. The research relied on data from the Pakistan Stock Exchange listings of 54 non-financial companies. Descriptive analysis revealed the characteristics of the data, revealing that it followed a normal distribution. The endogeneity issues were managed using the generalized method of moments (GMM). Managerial ownership, institutional ownership, [1]and ownership concentration were all shown to have a statistically significant effect on investment efficiency using the generalized method of moments (GMM). The mediation analysis results showed that FRQ is a significant mediator between institutional ownership and investment efficiency, FRQ is a partial mediator between ownership concentration and investment efficiency, and FRQ was not found as a mediator between managerial ownership and investment efficiency. High-quality financial reporting is shown to be a mediator between institutional ownership and investment efficiency, and the study’s findings imply that this effect may be maximized. The findings may be helpful in the business community in Pakistan and investors, practitioners, administrators, and academics interested in learning more about the quality of financial reporting and the standards of ownership characteristics processes.